Circus Workshop in the chid Psychiatry - Crusös Dora (Arteterapia)
The following paper is about the possible psychological effects of social circus, and our experiences with teaching circus methods in children psychiatry. In the beginning the paper try to place social circus in a wider theoretical frame, and searches for the place of it among psychological methods and therapies. We look at the wider and the more specific psychological constructs, what can be effected by social circus, especially the factors which are damaged in children with psycological or psychiatrycal problems. We examine the different parts of circus, how they can help in different problems. The further aim is to research the effects of a continuous social circus group, and to find it’s own way among psychotherapies.